IMPELMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN MELALUI EKSTRAKURIKULER PRAMUKA SISWA DI SMA NEGERI 02 KOTA PONTIANAK - Novita Sariani; Norsidi Norsidi (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2022)
The purpose of this research is to describe the implementation of environmental care character education through scout extracurricular and the obstacles faced by the coaches in environmental care character education activities through scout extracurricular at SMA Negeri 02 Pontianak City. The method in this research is a qualitative method. Data sources include informants, places/events, and documents. Technical data collection was obtained through in-depth interviews, observation, and document analysis. The sampling technique used was snowball sampling and purposive sampling. Data analysis in this study used an interactive model. The results of the research that the character education process is carried out through three stages, namely Moral Knowing, Moral Feeling, and Moral Action and applying the Scouting Method. The obstacles faced by the coaches in environmental care character education activities through scout extracurriculars at SMA Negeri 02 Pontianak City are that the material is a lot moreover with character education but the hours are few, the lack of awareness of the students to implement the character values of caring for the environment. Just touched on the level of recognition of norms or values. Lack of participation of parents and the community in supporting the cultivation of character education.